GAMABRAN MENTRUASI PENYINTAS COVID-19 DI FAKULTAS KEDOKTERAN UNIVERSITAS PEMBANGUNAN NASIONAL "VETERAN" JAKARTA - Ika Maulida, (2023)
Introduction: It has been reported that several female COVID-19 survivors experience changes in their menstrual cycle. This study aims to obtain an overview of menstruation among female COVID-19 survivor students at The Faculty of Medicine, Universitas Pembangunan Nasional "Veteran" Jakarta (FMUPNVJ). Method: This is a descriptive study using a retrospective design. The sample size of 32 individuals was taken entirely (total sampling). The criteria for the subjects were confirmed COVID-19 within the past year, aged 18-24 years, normoweight, unmarried, and without a history of illness or the use of hormonal contraception that affects the menstrual cycle. Data was collected using a questionnaire. Results: Out of the subjects, 18 (56.3%) had received three doses of vaccination, 21 (65.6%) had received the first and second doses of the Sinovac vaccine, 31 (96.9%) experienced mild symptoms (home isolation) during the COVID-19 infection, and 9 (28.1%) had been infected with COVID-19 twice. Menstrual changes experienced by subjects six months after being infected with COVID-19 included two subjects with prolonged cycles, 3 subjects with shortened cycles, 1 subject with decreased menstrual blood volume, 1 subject with increased menstrual duration, 5 subjects experiencing menstrual pain, and 2 subjects experiencing bleeding between two cycles. A total of 8 subjects reported recurring menstrual problems. There was a relationship between the frequency of COVID-19 infection and the number of menstrual problems (p = 0.02). Conclusion: Temporary menstrual changes occur in a small proportion of COVID-19 survivors.